Discussing a new direction for design management through a new design management audit framework - Topaloğlu, Fulden; Er, Özlem (Taylor & Francis, 2017)
Design management has evolved from the simple view as the management of design projects and processes, to include more upstream responsibilities and skills, at the intersection of design and strategic management. Recent literature highlights the role of design in leading and shaping company strategy, conceiving new business models, and in driving organizational change and renewal. Yet existing tools and frameworks for assessing design management capabilities fall short in catching up with the transition that has been undergoing in the ways design is utilized and managed inside organizations. This paper presents a new Design Management Audit Framework that aims to fill the gaps in existing tools by incorporating new capabilities that are increasingly emphasized by the emerging design, design management and strategic management literature. The tool also seeks to provide an answer to the question: "What are the new capabilities to be integrated into design management practices of our future economies?"
12th International Conference of the European-Academy-of-Design (EAD) -- APR 12-14, 2017 -- Sapienza Univ Rome, Fac Architecture, Rome, ITALY
WOS: 000419738000046
Keywords: Design Management; Strategic Design; Design Management Audit